MicroRNA-29a suppresses the growth of human cervical cancer cells by targeting cell division cycle 42 (CDC42) - Fang Song (Taylor & Francis Group, 2021)
Several microRNAs (miRs) play regulatory roles in cervical cancer. The present study investigated the molecular role of microRNA-29a in cervical cancer via modulation of cell division cycle 42 (CDC42) expression. The results showed significant (P < 0.05) downregulation of miR-29a human in cervical cancer cells. Overexpression of miR-29a inhibited the proliferation and colony formation of the cervical cancer cells via G0/G1 cell cycle arrest. In silico analysis and luciferase reporter assay showed CDC42 to be the molecular target of miR-29a. CDC42 was found to significantly (P < 0.05) overexpressed in cervical cancer cells. Nonetheless, miR-29 overexpression inhibited the expression of CDC42 in DoTc2 cells. Silencing of CDC42 inhibited the proliferation of DoTc2 cells. However, overexpression of CDC42 could prevent the tumour-suppressive effects of miR-29a. Finally, miR-29a was found to suppress the tumour-growth in vivo further confirming the tumour-suppressive effects of miR-29. Collectively, the findings of the present study revealed the tumour-suppressive effects of miR-29 of cervical cancer.